Trends in the epidemiology of pediatric severe sepsis - Hartman, Mary E; Linde-Zwirble, Walter T; Angus, Derek C; Watson, R Scott (Pediatric critical care medicine, 2013)
In the past decade, guidelines have been developed for the early detection and management of severe sepsis in children and neonates. However, severe sepsis continues to be a significant U.S. healthcare problem, accounting for over 720,000 annual hospitalizations. Large-scale epidemiologic studies of severe sepsis continue to be limited, particularly in children. We present data from 1995, 2000, and 2005 in seven U.S. states, examining how case mix, outcome, and resource use for pediatric severe sepsis have changed over time. We constructed a database including all acute-care hospitalizations for children in the seven states. For each case, we extracted data on demographic characteristics; the principal diagnosis, up to six secondary diagnoses, and six procedures as classified by the International Classification of Diseases, 9th Revision, Clinical Modification codes; and in-hospital fatality. We identified patients with severe sepsis using International Classification of Diseases, 9th Revision, Clinical Modification codes for both infection and acute organ failure. Retrospective observational cohort dataset from seven U.S. states from 1995, 2000, and 2005. Children in the U.S. 0-19 years old. None. In 2005, 17,542 children were hospitalized with severe sepsis in the seven states; there was an 81% increase in pediatric severe sepsis cases since 1995 and a 45% increase since 2000. This corresponded to an increase in prevalence from 0.56 to 0.89 cases per 1,000 pediatric population. Between 1995 and 2005, the prevalence of severe sepsis in newborns more than doubled, from 4.5 to 9.7 cases per 1,000 births. The most common infecting organisms in all 3 years were Staphylococcus species. From 1995 to 2005, the case-fatality rate decreased from 10.3% to 8.9%. Case fatality associated with Staphylococcus aureus increased, whereas fatality associated with Streptococcus pneumoniae decreased by 75%. Nationally, there were 75,255 pediatric hospitalizations in 2005 involving severe sepsis, with an associated cost of $4.8 billion. Between 1995 and 2005, the prevalence of severe sepsis in U.S. children steadily rose, due to a significant increase in the prevalence of severe sepsis in newborns.